If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1y + 2 = 5x Reorder the terms: 2 + -1y = 5x Solving 2 + -1y = 5x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1y = -2 + 5x Combine like terms: 2 + -2 = 0 0 + -1y = -2 + 5x -1y = -2 + 5x Divide each side by '-1'. y = 2 + -5x Simplifying y = 2 + -5x
| 3s^2+11s-14=0 | | 9a^2+a-3=0 | | 24q^2+37q=0 | | x+3=-y | | x-3/5y=0 | | 14g^2-3G-2=0 | | 4y+12x=4 | | (35x^2-21x)/(15x^2-9x) | | (10/3)^2 | | 149.99*1/3 | | (10/3)² | | 0.25(x+2)=0.5(5-x) | | 0.25(x-2)=0.5(5-x) | | 0.25(x-2)=0.5(5-a) | | 2y+3x=20 | | 5x=19+1 | | 7(t-3)+7t=7t(2t+5)-12 | | -4x(x^2-4x)=0 | | 5p(p-7)-7p(p+2)= | | 12ab/18a | | (x-3)(x+4)+(x-3)(x+2)=0 | | 3/5x-29/10-x | | 2x-13=-4+x | | (2x+1)(4.5x^2-9x-27.5)=y | | -4x+9y+19=0 | | 5(11x-2)=155 | | 4x+(-x)=9 | | 7c-8=17 | | 1/5(5x-4)=4-x | | 150=y+0.6y | | 501-50= | | 150=y+6y |